2002
DOI: 10.1029/2001jc001256
|View full text |Cite
|
Sign up to set email alerts
|

Deep flows in the Yucatan Channel and their relation to changes in the Loop Current extension

Abstract: The first attempt to establish a relation between the Loop Current extension and deep flows in Yucatan Channel was made by Maul et al. [1985]; it was unsuccessful, probably because of the low spatial resolution of their observations. From September 8, 1999, to June 17, 2000, eight moorings with acoustic Doppler current profilers, current meters, and thermometers were deployed across the Yucatan Channel. The data from these arrays were used to compute time series of the transports below the level of the deepest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 7 publications
14
92
1
2
Order By: Relevance
“…Maul et al [985] observed similar southward (deep) events and the apparent relation of these events to eddy shedding. More recent data and analyses [Bunge et al 2002;Ezer et al, 2003] support Maul et al's and Oey's [996] findings. Second, Oey noted that these transport fluctuations occurred at shorter periods (weeks ~ months) than eddy-shedding, i.e., not every Loop Current extension (and deep southward flow) resulted in shedding.…”
Section: Loop Current and Eddies In The Earlymentioning
confidence: 61%
“…Maul et al [985] observed similar southward (deep) events and the apparent relation of these events to eddy shedding. More recent data and analyses [Bunge et al 2002;Ezer et al, 2003] support Maul et al's and Oey's [996] findings. Second, Oey noted that these transport fluctuations occurred at shorter periods (weeks ~ months) than eddy-shedding, i.e., not every Loop Current extension (and deep southward flow) resulted in shedding.…”
Section: Loop Current and Eddies In The Earlymentioning
confidence: 61%
“…Bunge et al, [2002] found a very strong relationship between LC area and deep YC flows for their time frame. They attributed the lack of a relationship found…”
Section: Maulmentioning
confidence: 88%
“…Maul and Vukovich [1993] examined volume transport through the FLS and also did not find a significant relation to the LC area rate of change. Bunge et al, [2002] used a simple box model to illustrate Maul's [1977] theory. They investigated data from the Canek observing program, which deployed eight moorings with acoustic doppler current profilers and current meters across the YC from 8 September 1999 to 17…”
Section: Introductionmentioning
confidence: 99%
“…-T6 is in the lower thermocline and has been used as the interface for a two-layer system, separating deep waters from the more energetic upper layer containing mesoscale structures and the LC (Bunge et al, 2002;Donohue et al, 2008;Hamilton et al, 2016a, b). …”
Section: Detection Of Mesoscale Structuresmentioning
confidence: 99%